PEMBANGUNAN SISTEM INFORMASI INVENTORY MENGGUNAKAN LINEAR SEQUENTIAL MODEL UNTUK PENINGKATAN LAYANAN INVENTORY BARANG - Frieyadie Frieyadie (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2015)
Inventory data processing still using the book out and book incoming goods which have been provided by the company. Reporting is done by copying the data inventory of books into Microsoft Office Excel Search files that have been saved and retyping existing report requires a long time in the delivery of information. Each monthly reports in Excel format should be sent via email. The system can not know the make inventory data updates per day. existing inventory must be balanced with the need because the inventory is too much will result in the company bears the risk of damage and high storage costs in addition to the cost of investments. The purpose of the research conducted: Solve problems that arise in the inventory system, giving the proposed computerized system to inventory system, and the administration gets applications that can be used in the recording, processing, and storage, and reporting of IT goods in and out relatively accurately.